Seed Yield and Economic Performance of Castor at Farmers’ Field in Arid and Semi-arid Regions of Rajasthan - Ram, Moola; Meena, Durgashankar (Annals of Arid Zone, 2021)
Frontline demonstrations on improved practices of castor were conducted in Jodhpur, Jaisalmer and Sirohi districts of Rajasthan. The mean seed yield of castor ranged from 3680 to 4071 kg ha-1 under improved practices and 3000 to 3786 kg ha-1 under farmers’ practices. Among hybrids, the maximum mean seed yield of 3874 kg ha-1 was produced by DCH 519 followed by Commando, Sagar Moti, MRCA 409, DCH 177 and GCH 7 with 3786, 3588, 3393, 3363 and 3000 kg ha-1 seed yield, respectively. Under improved practices, maximum seed yield of castor was 3803 kg ha-1 in Jodhpur district followed by 3781 kg ha-1 in Jaisalmer district and 3408 kg ha-1 in Sirohi district. The overall productivity of the castor demonstrations was 3664 kg ha-1 under improved practices and 3874 kg ha-1 under hybrids which was 22.2% and 8.2% higher respectively, over farmers’ practices (2998 and 3581 kg ha-1, respectively). Key words: Farmer’s field, castor, seed yield, frontline demonstration, castor hybrids.